Chapter 9 The Instrumental Use of Incorporation Philosophies in a Multicultural Norway - Page, Alexander Gamst; Chahboun, Sobh (Taylor & Francis, 2025)
This book explores the disjuncture that emerges at various levels in European diversity management policies and their translation into practice. It shows that state-wide strategies can only guide diversification outcomes, not wholly control them, and in practice, national level integration policies rely on multi-level involvement including authorities at regional or local levels and civil society organisations. The book demonstrates a complex and varied picture of the ways in which different European countries engage with ethnic diversity, as well as to the internal (in)consistency of the philosophical underpinnings of this engagement. As such, it draws attention not just to ways in which diversity "is done," but illuminates processes and narratives which are messy, contested, and contradictory. This book is of key interest to scholars, students, and practitioners involved in integration, ethnic and cultural diversity studies, migration and immigration, citizenship, ethnicity, and more broadly to European studies, and the wider social sciences.